Peran Aktor Kebijakan dalam Implementasi Program Beasiswa Mahasiswa Berprestasi Kabupaten Wonogiri Tahun 2020 - Dwi Nurhayati; Sri Yuliani (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
This study discusses the Role of Policy Actors in the Implementation of the Wonogiri Regency Student Achievement Scholarship Program in 2020. The purpose of this research is to examine the side of the role of policy actors by using actor role theory in the implementation of Eden & Ackerman. The theory states that the role of implementing actors will be divided into the roles of key players, context setters, subject and crowd actors. This study uses descriptive qualitative research methods with data collection techniques through interviews, observation and documentation studies. In the technique of determining informants, this study used a purposive sampling technique. In this study, it was analyzed through the analysis of the interactive model of Milles and Huberman. The results of the study show the role of policy actors. The roles of actors involved in the implementation of the scholarship program for outstanding students in Wonogiri Regency can be categorized based on the level of importance and influence. The policy actors include the Wonogiri Regency Youth, Sports and Tourism Office, the Wonogiri Regency Active Scholarship Recipients (IMAPRES), the Wonogiri Regency Education and Culture Office, and the Wonogiri Regency Achievement Student Scholarship Program Passive Recipients.